UMP virtual directory in augmented reality - Kit, Thium Keng (2013)
UMP virtual directory in augmented reality (AR) project is developed to provide a platform for students to easily get to know the university campus building information and avoid students from searching through internet or directly asking. The purpose of this project is to develop an interesting AR system. The objectives of this system are to enhance the information provided by the university and help students to find out the function of each UMP campus building. A survey questionnaire was carried out among UMP students and the finding is that most of the students does not actually care or use about UMP map board. By compared to this conventional way, the new system will be more convenient and attractive to be use. A student does not need to always refer to UMP map board when they are lost direction or does not know what the building for. This AR virtual directory offers interaction with the marker which enables students experiences a new way to understand the campus buildings. It will assist students to find the right information of the campus building.